Illocutionary Speech Acts in Indonesian Language Learning at High School - Dewa Ayu Widiasri (e-Journal of Linguistics, 2020)
The purpose of this study is to describe the types ofillocution in the form of verbal speech acts between teachersand students in learning Indonesian language at Senior HighSchool 1- Tampaksiring, Gianyar, Bali. This study applieddescriptive qualitative analysis with the support of audio-visual recordings technique, observation methods,documentation methods that combined with pragmatics andclassification techniques. The results of the study haveshown that the types of illocution, with the order of use, aredirective function (40%), expressive (25%), assertive (20%),commissive (10%), and declarative (5%) in teacher andstudent speech acts.